Oxidative stress and some biochemical parameters during starvation and refeeding in Astacus leptodactylus (Esch., 1823) - Barim-Oz, O.; Sahin, H. (C M B Assoc, 2016)
This study was conducted to determine the effect of starvation (78 days) and refeeding (33 days) on oxidative stress (malondialdehyde (MDA)), antioxidants (superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GSH-Px)), arginase (AR) and nitric oxide (NO) in the hepatopancreas, muscle and gills tissues of freshwater crayfish (Astacus leptodactylus). Crayfish were maintained at three experimental groups: control (fed), starved (not fed) crayfish for 78 days and refeeding crayfish for 33 days after 78 days starvation. The biochemical analysis in the tissues were measured at 3, 18, 33, 48, 63 and 78 days of starvation and feeding and at 3, 18 and 33 days of refeeding. In the all periods, the MDA levels were significantly higher in tissues of starved crayfish than the control ones. Significant changes in the MDA levels were also observed amongst starvation times. In the tissues of starved crayfish was significantly higher SOD, CAT, GR and AR activities when compared to control crayfish. The GSH-Px and NO activity showed increases and decreases in different starvation periods according to control group. The parameters measured returned to control values after 33 days of the refeeding. Collectively, the present study indicated that starvation induces MDA, SOD, CAT, GSH-Px, GR, AR and NO activity in the tissues, and A. leptodactylus exposed to starvation can be withstand 78 days.
Keywords: Crayfish; Starvation; Enzymatic Antioxidants; Oxidative stress